Extending high fatty foods shelf-life protecting from lipid oxidation and microbiological contamination: an approach using active packaging with pomegranate extract - Andrade, Mariana A. (2023)
The search for new forms to extend foodstuffs’ shelf-life through the use of natural compounds and extracts continues to grow among researchers and the industry. In this line of thought, the main objective of this work was to develop, characterize and evaluate the effectiveness of an active food packaging based on polylactic acid (PLA) and incorporated with natural extracts obtained from grape and/or pomegranate by-products. In vitro, antioxidant methods were applied to evaluate the antioxidant capacity of three extracts: wort extract, freeze-dried pomegranate peels extract (PPE-FD), and natural pomegranate peels (PPE-N). Punicalagin (A + B) and ellagic acid were determined in PPE-FD, PPE-N, and active films by UHPLC-DAD. New PLA-based active packaging with PPE-FD (PLA/3PPE) and pomegranate peels (PLA/3PP) were developed, and their chemical, mechanical, and barrier properties were evaluated. Moreover, the effectiveness of the new film was carried out through the study of lipid oxidation state and microbial contamination of two high-fat content foodstuffs, almonds and beef meat. PPE-FD presented high antioxidant capacity and high content in total phenolics and flavonoid compounds. The PLA/3PPE and PLA/3PP prevented the lipid oxidation of meat and presented antimicrobial activity against Staphylococcus aureus. The addition of the PPE-FD and the pomegranate peels to the PLA did not affect the morphology of the polymer. Although both PPE-FD and pomegranate peels presented punicalagin (A + B) and ellagic acid, only ellagic acid was identified and quantified in the active PLA. Active PLA films were not effective in delaying the lipid oxidation of almonds, but they showed to be significantly effective in delaying the lipid oxidation of beef meat and reducing the microbial growth in this food matrix over time.